Why Does Pnemococcus Kill? - Yves Bergeron; Michel G Bergeron (Canadian Journal of Infectious Diseases)
Acute lower respiratory tract infections remain the most common cause of death due to infection worldwide, and Streptococcus pneumoniae is responsible for approximately 30% of all cases of community-acquired pneumonia. While many virulence factors have been associated with fatal pneumococcal pneumonia. there is growing evidence that some components of the immune response contribute significantly to the high mortality rate. This paper reviews the major bacterial virulence factors and pathogenesis steps that characterize fatal pneumococcal pneumonia, with a focus on the inflammation that was observed from the initial infection to death in an experimental murine pneumonia model. These steps involve the successive recruitment of polymorphonuclear neutrophils (PMNs). monocytes and lymphocytes; the pulmonary and/or systemic release of inflammatoty mediators that characterize the prebacteremic and bacteremic phases of infection; and the participation of parenchymal cells in the host response. Although the kinetics of cytokines differ considerably from blood to lung tissue to alveoli, and blood levels do not correlate to tissue levels, the kinetics of tumour necrosis factor (TNF) and interleukin-6 in blood, as well as TNF and nitric oxide in bronchoalveolar lavage (BAL) fluid are good indicators of the evolution of the disease. Nitric oxide release is biphasic and corresponds mostly to monocyte recruitment in BAL fluid and concomitant serious tissue injury. Pneumococci activate leukotriene B4 (LTB4) release. but PMN recruitment is not primarily mediated by LTB4. Bacteremia, leukopenia, thrombocytopenia and lipid peroxidation closely precede death. Knowledge of the chronology of microbiological and inflammatory events that occur during pneumonia may help to design appropriate diagnostic tests that could be used to monitor the evolution of this deadly infection. There has been an explosive growth in the use of biological response modifiers that may be given to treat pneumonia. The proper use of these agents requires prior identification of biological markers in humans with pneumonia.